2016
DOI: 10.1038/jid.2015.389
|View full text |Cite
|
Sign up to set email alerts
|

Connexin26 Mutations Causing Palmoplantar Keratoderma and Deafness Interact with Connexin43, Modifying Gap Junction and Hemichannel Properties

Abstract: Mutations in GJB2 (Cx26) cause either deafness, or deafness associated with skin diseases. That different disorders can be caused by distinct mutations within the same gene suggests that unique channel activities are influenced by each class of mutation. We have examined the functional characteristics of two human mutations, Cx26-H73R and Cx26-S183F, causing palmoplantar keratoderma (PPK) and deafness. Both failed to form gap junction channels or hemichannels when expressed alone. Co-expression of the mutants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
56
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(69 citation statements)
references
References 64 publications
8
56
0
Order By: Relevance
“…For example, Cx26 mutations, G12R/N14Y or H73R/S183F, directly caused keratitis-ichthyosis-deafness and PPK syndrome, respectively. During these syndromes, Cx26 mutants may interact with Cx43 more efficiently and exacerbate Cx43 hemichannel activity, thus increasing cell membrane permeability and resulting in ATP release and Ca 2+ overload (14,15). These studies further demonstrate the important role of Cx43 in genetic skin disorders.…”
Section: Cx43 In Keratodermamentioning
confidence: 69%
See 1 more Smart Citation
“…For example, Cx26 mutations, G12R/N14Y or H73R/S183F, directly caused keratitis-ichthyosis-deafness and PPK syndrome, respectively. During these syndromes, Cx26 mutants may interact with Cx43 more efficiently and exacerbate Cx43 hemichannel activity, thus increasing cell membrane permeability and resulting in ATP release and Ca 2+ overload (14,15). These studies further demonstrate the important role of Cx43 in genetic skin disorders.…”
Section: Cx43 In Keratodermamentioning
confidence: 69%
“…121014). The normal expression (10), proper location (13) and accurate connection with other Cxs (14,15) are crucial for its function.…”
Section: Regulation Of Cx43mentioning
confidence: 99%
“…However, co-expression of the mutants with Cx43 showed significantly increased hemichannel activity in the presence of either mutant, compared to Cx43 alone. Co-immunoprecipitation experiments showed that Cx43 could be pulled down more efficiently with Cx26-H73R and Cx26-S183F than wild-type Cx26, confirming the enhanced formation of heteromeric hemichannels [30]. This result was surprising, as previous reports had shown that wild-type Cx26 was unable to co-oligomerize with Cx43 [34], and Cx43 expression failed to induce voltage-activated hemichannel currents in Xenopus oocytes [35].…”
Section: Functional Consequences Of Connexin Mutations In Congenitmentioning
confidence: 78%
“…Four of the five showed dominant-negative inhibition of co-expressed wild-type Cx26, suggesting a mechanism for their contribution to hearing loss. When these mutations were co-expressed with Cx43, they all produced trans-dominant inhibition of Cx43 gap junction channels [28-30]. This suggested that skin disease caused by PPK mutations might be manifested through a common gain of function mechanism where the Cx26 mutations dominantly interact with other connexins, such as Cx43.…”
Section: Functional Consequences Of Connexin Mutations In Congenitmentioning
confidence: 99%
“…It is of note then that at the edges of human chronic wounds Cx43, 26 and 30 are strikingly upregulated in the epidermis, as well as Cx43 in the dermis [81]. It is also possible that in some cases, aberrant heteromerization of Cx43 and Cx26 may underlie pathology, for example in keratitis-ichthyosis-deafness syndrome [82] and palmoplantar keratoderma and deafness [83], thereby extending the potential influence of Cx43 antisense and peptide technologies to disorders ascribed to other Cxs. Dysregulated connexin expression appears to be common feature in chronic skin wounds.…”
Section: Reducing Cx43 Levels Improves Healing Of Epithelial Tissuesmentioning
confidence: 99%